Analysis of value-added services of power communication network in energy internet - Hong ZHU; Qi SHAO (Dianxin kexue)
The value-added services of power communication networks in the energy internet were introduced.5G,4K/8K ultra high definition video,business that cloud drive all-optical network construction were analyzed.How the power company uses its resource advantages to expand energy internet value-added services and their business models were analyzed,including infrastructure resource leasing,backbone line business leased line,FTTH wholesale and telecommunication business,data center leasing,etc.Based on ubiquitous electric internet of things,power company that could combine big data and artificial intelligence to expand more value-added services was forcasted.